Number of Bacteria and Time of Coincubation With Bacteria Required for the Development of Acanthamoeba Keratitis. Issue 3 (March 2017) - Nakagawa, Hayate; Hattori, Takaaki; Koike, Naohito; Ehara, Tomoko; Narimatsu, Akitomo; Kumakura, Shigeto; Matsumoto, Tetsuya; Goto, Hiroshi
Abstract : Purpose: We hypothesized that bacteria may be a factor contributing to the development of Acanthamoeba keratitis (AK). We investigated interactions between Acanthamoeba and Pseudomonas aeruginosa for the development of keratitis in rabbit corneas. Methods: Acanthamoeba castellanii (ATCC50492) and P. aeruginosa (PAO-1) were used. Two densities of P. aeruginosa (high, 1 × 10 8 /mL; low, 3 × 10 5 /mL) and 2 durations of coincubation (long, 6 h; short, 2 h) of Acanthamoeba with 1 × 10 8 /mL of P. aeruginosa were tested. Acanthamoeba alone or Acanthamoeba coincubated with P. aeruginosa was inoculated into rabbit corneas. After inoculation, levofloxacin (LVFX) eye drops were administered. The clinical score of the cornea was evaluated after inoculation. Results: Acanthamoeba alone did not produce keratitis during a 5-day observation period. Rabbit corneas inoculated with Acanthamoeba coincubated with low-density P. aeruginosa followed by topical LVFX were clear with few infiltrates. Corneas inoculated with Acanthamoeba coincubated with high-density P. aeruginosa followed by LVFX treatment developed severe keratitis, and clinical scores were significantly higher compared with high-density P. aeruginosa alone followed by LVFX treatment (scores 7, 9.6, 8.5 vs. 3, 3.5, 3.25 on days 1–3, all P < 0.01). The long (6 h) coincubation time of Acanthamoeba with high-density P. aeruginosa resulted in more severe keratitis compared with short (2 h) coincubation (scores, 9.7, 12.7, 12.1, 9.8, 8.7 vs. 7, 9.6, 8.5, 6.9, 5.6 on days 1–5, all P < 0.01). Conclusions: These results suggest that the presence of bacteria is essential and a critical number of bacteria is required for the development of AK. The time of coexistence with bacteria may be an important determinant of the severity of AK. Abstract : Supplemental Digital Content is Available in the Text.